О системном подходе при разработке и полигонных испытаниях бортовых автоматизированных корабельных комплексов обнаружения и целеуказания - Додонов, А.Г.; Путятин, В.Г. (Реєстрація, зберігання і обробка даних, 2017)
Рассмотрены вопросы анализа и развития основных научных проблем разработки методологии системного проектирования и полигонных испытаний бортовых автоматизированных корабельных комплексов обнаружения и целеуказания. Розглянуто питання аналізу та розвитку основних наукових проблем розробки методології системного проектування та полігонних випробувань бортових автоматизованих корабельних комплексів виявлення та цілевказування. Questions related to the analysis of the main scientific problems of the development and testing of automated shipborne detection and target design complexes consisting of subsystems and devices on dissimilar physical principles of functioning are examined. In particular, it has been considered such aspects as the principles of the system approach when choosing the optimal technical appearance of the complex (structure, composition and degree of redundancy of the subsystems included in the complex), the development of a coherent methodology for designing and testing the complex on a unified system basis; the development of theoretical bases and mathematical models for the study of the structural and functional construction of the complex as a whole and its subsystems; development and research of methods, models and algorithms for the selection of optimal for the set of additive quality indicators of the technical imp-lementation of the system; development and research of the methods, models and algorithms for analyzing the structural reliability of a complex as a system with a complex structural organization, with fairly general assumptions regarding the laws for distributing fail-safe times and restoring component parts of the complex; the strategy of choosing the optimal ways of development of the experimental and test base for complex testing.